The drusenlike phenotype in aging Ccl2-knockout mice is caused by an accelerated accumulation of swollen autofluorescent subretinal macrophages. - Luhmann, U; Robbie, S; Munro, P; Barker, SE; Duran, Y; Luong, V; Fitzke, F; Bainbridge, J; Ali, R; Maclaren, R (2009)
PURPOSE: Drusen, which are defined clinically as yellowish white spots in the outer retina, are cardinal features of age-related macular degeneration (AMD). Ccl2-knockout (Ccl2(-/-)) mice have been reported to develop drusen and phenotypic features similar to AMD, including an increased susceptibility to choroidal neovascularization (CNV). This study was conducted to investigate the nature of the drusenlike lesions in vivo and further evaluate the Ccl2(-/-) mouse as a model of AMD. METHODS: The eyes of 2- to 25-month-old Ccl2(-/-) and C57Bl/6 mice were examined in vivo by autofluorescence scanning laser ophthalmoscopy (AF-SLO) and electroretinography, and the extent of laser-induced CNV was measured by fluorescein fundus angiography. The retinal morphology was also assessed by immunohistochemistry and quantitative histologic and ultrastructural morphometry. RESULTS: The drusenlike lesions of Ccl2(-/-) mice comprised accelerated accumulation of swollen CD68(+), F4/80(+) macrophages in the subretinal space that were apparent as autofluorescent foci on AF-SLO. These macrophages contained pigment granules and phagosomes with outer segment and lipofuscin inclusions that may account for their autofluorescence. Only age-related retinal pigment epithelium (RPE) damage, photoreceptor loss, and sub-RPE deposits were observed but, despite the accelerated accumulation of macrophages, we identified no spontaneous development of CNV in the senescent mice and found a reduced susceptibility to laser-induced CNV in the Ccl2(-/-) mice. CONCLUSIONS: These findings suggest that the lack of Ccl2 leads to a monocyte/macrophage-trafficking defect during aging and to an impaired recruitment of these cells to sites of laser injury. Other, previously described features of Ccl2(-/-) mice that are similar to AMD may be the result of aging alone.